Evaluation of Antioxidant Activity of Beta vulgaris Root Extract in Rats - Ashoka Babu, V.L.; Gowri, R. (Asian Journal of Chemistry, 2010)
The antioxidative activity of the mewthanolic extract of Beta vulgaris roots (MEB) was investigated in rats with carbon tetrachloride (CCl4) induced erythrocyte damage. Simultaneous intraperitoneal administration of the crude extracts (100 and 200 mg/kg body weight/day) with CCl4 (1 mL/kg of body weight) to rats for alternate days of two weeks prevented the loss of functional integrity and membrane lipid alteration in red blood cells induced by oxidative stress. Beta vulgaris extract inhibited the accumulation of lipid peroxidation products in the plasma as well as maintained the activities of antioxidant enzymes such as superoxide dismutase (SOD) and catalase. The extracts further had the ability to decrease the membrane fluidity induced by CCl4. It can therefore be suggested that the root extract of Beta vulgaris possess an erythrocyte protective activity against drug induced oxidative stress.